Material Aspects of Building and Craft Traditions: A Himalayan Case Study - Feiglstorfer, Hubert (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Due to its diverse natural conditions, the Himalayas are particularly suitable for research on craft traditions. The book clearly shows connections between natural and cultural parameters and regional building and craft traditions and their influence on the material culture in the Himalayas.